2016
DOI: 10.1080/1828051x.2016.1186505
|View full text |Cite
|
Sign up to set email alerts
|

Body measurements from selective hunting: biometric features of red deer (Cervus elaphus) from Northern Apennine, Italy

Abstract: Morphometric studies on European red deer (Cervus elaphus L.) living in sub-Mediterranean areas are rare. In this paper, we provide the first morphometric description of red deer from Apennine living in Prato Province, as well as a description of its skeletal growth pattern. We analysed 18 body, cranial and antler measurements from 905 deer carcasses, collected during 12 hunting seasons (2000-2012). The body size of red deer from Prato appeared comparable to that of other populations from Northern Apennine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…In agreement with Becciolini et al . [ 60 ], the HFL and LJL of GR's red deer population mainly increase during the juvenile phase. Unexpectedly and in contrast to Pettorelli et al .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with Becciolini et al . [ 60 ], the HFL and LJL of GR's red deer population mainly increase during the juvenile phase. Unexpectedly and in contrast to Pettorelli et al .…”
Section: Discussionmentioning
confidence: 99%
“…The collaboration of hunters in the measurement of the body parameters of their catch, and the use of these data for biometric analysis are useful tools to evaluate population features (Hewison et al 1996;Morellet et al 2007;Becciolini et al 2016). To formulate better wildlife management practices, it is very important to incorporate biometrics in structured databases and to analyze the collected information related to the autumn-winter food availability.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, the dimensions and shapes of structures in wildlife populations have been extensively investigated [1][2][3][4][5][6]. Biometric surveys and analysis of the resulting cranial and body data are now crucial in wildlife management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of wildlife populations [7] has, therefore, caused a general development in hunting activities, together with the necessity of using biometry (size analysis) and geometric morphometry (shape analysis) as methods to monitor the status of wildlife populations and suitable environments for different wildlife species [9][10][11][12]. The morphometric data analysis provides information on skeletal development and allows the identification of body measures useful as ecological indicators, permitting the formulation of better management strategies for wildlife [2]. Previous research demonstrated a relationship between biometric parameters (e.g., body mass, cranial and skeletal measures) and environmental features (e.g., climate, habitat quality, autumn-winter food availability) [2,5,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation